Knee Joint Vibroarthrographic Signal Processing and Analysis - Wu, Yunfeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book presents the cutting-edge technologies of knee joint vibroarthrographic signal analysis for the screening and detection of knee joint injuries. It describes a number of effective computer-aided methods for analysis of the nonlinear and nonstationary biomedical signals generated by complex physiological mechanics. This book also introduces several popular machine learning and pattern recognition algorithms for biomedical signal classifications. The book is well-suited for all researchers looking to better understand knee joint biomechanics and the advanced technology for vibration arthrometry. Dr. Yunfeng Wu is an Associate Professor at the School of Information Science and Technology, Xiamen University, Xiamen, Fujian, China.
Introduction -- Signal Acquisition and Preprocessing -- Signal Analysis -- Feature Computing and Signal Classifications -- Summary and Research Directions.
Keywords: Engineering; Rehabilitation medicine; Pattern recognition; Biomedical engineering; Engineering; Biomedical Engineering; Rehabilitation Medicine; Signal, Image and Speech Processing; Pattern Recognition; Electronic books